Deformation and collapse of rock slopes considering weak plane orientation - Chang, Kuang-Tsung; Yeh, Po-Tsun; Hsiao, Yu-Shen; Wang, Chao-Yu; Chiu, Ya-Chu (Frontiers in Earth Science, 2024)
Some slopes experience multiple slides without collapse, while other slopes collapse once they are unstable. The early warning of slope collapse is a difficult but important subject. Considering the influence of weak planes on rock slope deformation and collapse is helpful for interpreting the behavior of deep-seated landslides and designing an early warning system. To investigate the deformation behavior of rock slopes with consideration on weak planes, artificial cemented sand plates were produced and stacked to form physical slope models with different weak plane orientations, where inclined loading was applied to induce the deformation and collapse of the slope. In addition, the deformation of real slopes was examined based on topographic features. The average strain at collapse is referred to as the critical strain, whose value changes for various slopes. Sorted by critical strain in descending order, the slope models include an anaclinal slope with 60° weak planes, an anaclinal slope with 30° weak planes, a cataclinal slope where the 30° weak planes coincide with the slope face, and a cataclinal slope with daylighting 20° weak planes. Similar to the experimental results, anaclinal slopes also present greater average strain values than cataclinal slopes for real slopes. A smaller critical strain implies a higher possibility for slope collapse when unstable. Local deformation does not always lead to collapse, but as the average velocity and the average strain rate of the sliding body increase, or the velocity ratio (VR) between the upper and lower parts of the sliding body approaches 1, a sliding surface inside the slope is likely developing and coalescing. Hence, such deformation features may contribute to a landslide warning system.